Plataforma peopleminin : recruitment analytics e gestão do conhecimento - Fagundes, Alexandre Gonzalez (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence